Analisis Struktur dan Pertumbuhan Ekonomi di Kota Payakumbuh Berdasarkan Sektor Lapangan Usaha - Rika Fitriani; Roza Zulfita; Neng Kamarni (Fakultas Sastra Universitas Ekasakti, 2021)
This study aims to see the economic structure and rate of economic growth based on industry in Payakumbuh Municipality. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS) 2012-2019. Descriptive data processing and analysis using the Location Question (LQ) method, grouping the industry sector with Klassen typology and measuring inequality with the Williamson Index. The results showed that the growth rate in the Municipality of Payakumbuh tends to increase every year, the sectors that provide the largest contribution to GRDP are the wholesale and retail sector, car and motorcycle repair, and from the results of the typology class sectors in quadrant I are advanced sectors. and rapid growth in the sectors of construction, wholesale and retail trade, repair of cars and motorbikes, information and communication, financial services and insurance, health services and social activities. Regional inequality with the Williamson index obtained which means that regional inequality is low.